Rofhani Pendomestikasian Perempuan dalam Narasi Antifeminisme Kanal YouTube Muslimah Media Center: Analisis Kritis Perspektif Fatima Mernissi - Rofhani Rofhani; Almas Sharfina 'Alaniah (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2023)
This article illustrates how the YouTube platform, particularly the Muslimah Media Center channel of Hizbut Tahrir Indonesia, has become the main platform for spreading anti-feminist narratives that relegate women to domestic roles. In the context of Indonesia's predominantly Muslim society, this narrative interprets feminism as a threat to Islam, creating tension between traditional values and social change. This article analyzes how the language, symbolism, and narratives used in Muslimah Media Center's YouTube content can influence perceptions and expectations of women in society. While there are diverse views within the platform, there are concerns that narratives that promote the